Pengaruh teknologi berbasis artificial intelligence terhadap kemampuan pemahaman konsep matematis pada siswa SMA dengan perilaku nomophobia - Ghaziya Astriningtyas; Sri Adi Widodo; Fitria Sulistyowati (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2026)
Studies examining changes in mathematical abilities among students with high levels of nomophobia through AI-based intervention designs remain very limited. This study aims to identify the effect of AI technology on the mathematical conceptual understanding of students with high nomophobia tendencies. This study employed a Single Subject Research method with an ABA design consisting of baseline 1, intervention, and baseline 2 phases. The subject was a student with nomophobia selected purposively. Data were collected through mathematical conceptual understanding tests in each session and analyzed visually within and across conditions. The results showed that in phase A1, the subject experienced difficulties in understanding function concepts. In phase B, conceptual understanding improved, although the subject still had difficulty representing functions in graphical form. In phase A2, the subject’s performance was more stable than in phase A1, indicating retention after the intervention ended. Thus, AI-assisted learning had a positive impact on improving students’ mathematical conceptual understanding.